The Level Of Mass Media Usage and The Role Of Communication Of Cattle Farmers Group Members in Cattle Supervisory Communication Network - A. Saleh (Institut Pertanian Bogor, 2008)
The cattle agribusiness supervision activities, similar to other types of supervision are supposed to undergo a communication structure changes. The communication pattern is no longer in the form of